Gestión financiera y la toma de decisiones en la empresa Inversiones Valentina & Nathaly SAC Pucallpa año 2022 - Cumapa Silvano, Juan Carlos (2022)
The objective of the research was to determine the relationship between financial management and decision making in the Empresa Inversiones Valentina & Nathaly SAC Pucallpa year 2022, opting to be an applied type study, descriptive level - correlational and non-experimental design; I include 24 administrative workers as a study population, for data collection the survey was used as a technique and the questionnaire as an instrument. Concluding that, financial management is rated as regular (25%) since the company sometimes directs its goals and actions to improve financial management; also, sometimes collects and organizes all the financial information before preparing the financial statements. Regarding decision-making, it is qualified as regular (21%), because the manager always demonstrates sufficient experience to guide decisions, and during his financial management he has almost always established financing policies, but never assumes financial risks as well as never they are evaluated. In the same way, it has been determined that there is a significant relationship between financial management and decision making, which has been corroborated by Pearson (r=0.754; p=0.000) at a considerable positive level.